STRUCTURAL-DYNAMIC ANALYSIS OF THE DOMESTIC CONSUMER MARKET IN THE CONTEXT OF MACROECONOMIC DEVELOPMENT OF UKRAINE - KLEPANCHUK, OLHA; ILCHYSHYN, STEPAN; DALYK, VOLODYMYR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the multifactor structural-dynamic analysis of the development of the consumer market of Ukraine as a system segmented into the markets of food and non-food goods and consumer services, and to determine the factor impact of its segments on macroeconomic dynamics. The stable growth of the analyzed segments was revealed, despite a slight decrease in the volume of sales of services in 2020 due to the quarantine restrictions imposed by the Government for certain types of economic activity. Changes in the commodity structure of the consumer market are analyzed. The average growth rate of food sales was 113.5 %, non-food – 111.2 %, services – 102.5 %, which is fully correlated with the average growth of nominal GDP by 118.1%. It was found that the largest share of household expenditures was concentrated in the food market, where there was a faster growth in consumer prices compared to effective demand. It was found that the average monthly total expenditures of households in the consumer market decreased, primarily on non-food goods and services. In the domestic market of consumer services, there was a tendency to widen the gap between market supply and effective demand and redistribute the structure of consumer demand. To obtain an objective description of the impact of the domestic consumer market on the general parameters of the economic system of Ukraine, the factor influence of sales in consumer markets of food and non-food goods and services on GDP dynamics is analyzed. The significance of the parameters of the regression equation was checked by Fisher’s F-test. It was found that despite the significant aggregate influence of external factors, the obtained regression equation with a high degree of reliability indicates that the state of the consumer market of food products has little effect on nominal GDP, while the growth of non-food and services markets is guaranteed to increase GDP. This allows us to rethink the role of the domestic consumer market as a concept of a holistic system of socio-economic relations, which complements the established location of the interaction of producers and consumers with the institutional component. Further research is recommended to be directed in the direction of an extremely important aspect of goal-setting of institutional regulation of domestic consumer market development, namely meeting the needs of consumers, who are the final link in market relations.